Remixing News: Appropriation and Authorship in Finnish Counter-Media - Seuri, Olli (2022)
This article outlines a first attempt at analysing counter-media publishing through the lens of remix theory. We concentrate on two key concepts—appropriation and authorship—which have a permanent standing in the remix research literature. To support our theoretical analysis, we investigate the coverage of two cases in the Finnish right-wing counter-media online publication MV-lehti. Our findings enable new readings on the nature of both counter-media work and remix culture. In fact, counter-media publishing leans more in the direction of remix culture—which is based on the act of using pre-existing materials to produce something new—than towards traditional journalistic convention, with its rules and ethical guidelines. MV-lehti’s practice of combining and layering different material is discernibly political, often resembling media activism. Our study provides the argument that counter to the utopian democratising assumptions of remix culture, the proliferation of remix practices has also given antidemocratic actors the means to challenge collectively and institutionally supported ideas of knowledge and justice. Counter-media publishing is perhaps democratising in that it offers the means to participate, but these antagonistic actors also remix news to undermine liberal-democratic ideals and social justice. Evidently, remix practices can be co-opted for a reactionary agenda.